Volumetric estimation of an intensive apple orchard with GIS - Riczu, P.; Bozsik, É.; Gálya, B.; Rásó, J.; Csiha, I.; El Shal, A. M.; Nyéki, J.; Tamás, J. (International Journal of Horticultural Science, 2013)
Remote sensing instruments and methods have become widespread in all segments of agriculture and horticulture. Among the innovative development of remote sensing instruments, the 3D laser scanner is one of the newest technique, which overtop in the spatial data collection. Terrestrial laser scanning is an appropriate tool for identifying such biophysical parameters like the structure of trees and branches, growth of volume. Determination of these parameters are time consuming and complicated with traditional methods. The examination was carried out in the Study and Regional Research Farm of the University of Debrecen near Pallag. We used Leica ScanStation C10 terrestrial laser scanner to estimate volumetric properties of the intensive apple orchard. Two rows of the study area were surveyed, where the height and stem diameter of apple trees were measured with Geomagic Studio 12 GIS Demo Software. Based on the built-in algorithms, the volume of each tree were defined by the software. The measured and calculated data was correlated, and middle correlations were detected. Estimated volume results could be useful for further investigation such as CO2 fi xing, which is an important factor for ecological service of the plantation.